An Islamic Criminal Law Review of Sasi Violations in Iha Village - Rita, Rita Defriza; Ahmad Faisal; Ade Arga Wahyudi (Al-Iftah: Journal of Islamic studies and society, 2025)
This study examines the sasi system as a customary legal mechanism within the community of Desa Iha, Maluku, and analyzes the nature of its violations through the lens of Islamic criminal law. Sasi is a local tradition aimed at preserving natural resources through collective prohibitions agreed upon by the community. Using a descriptive-qualitative approach, the research employed observation, in-depth interviews, and document analysis. The findings reveal that violations of sasi continue to occur, including theft, hoarding, and premature harvesting of protected crops. Customary sanctions such as fines and confiscation serve both preventive and corrective functions, aligning with the Islamic concept of ta‘zīr punishments. From the perspective of maqāṣid al-sharī‘ah, these violations may also be categorized as fasād fī al-arḍ (corruption on earth), as they damage both social order and ecological balance. Thus, integrating customary law and Islamic criminal principles presents a strategic approach to strengthening resource management systems grounded in justice and sustainability